2018
DOI: 10.12659/msm.910764
|View full text |Cite
|
Sign up to set email alerts
|

Diosmetin Attenuates Akt Signaling Pathway by Modulating Nuclear Factor Kappa-Light-Chain-Enhancer of Activated B Cells (NF-κB)/Inducible Nitric Oxide Synthase (iNOS) in Streptozotocin (STZ)-Induced Diabetic Nephropathy Mice

Abstract: BackgroundWe evaluated the nephroprotective effect of diosmetin in streptozotocin (STZ)-induced diabetic nephropathy (DN) mice.Material/MethodsDiabetes was induced by injecting STZ (50 mg/kg) i.p. for 5 days. Biochemical parameters, such as fasting blood glucose, creatinine, BUN in the serum, and albumin in the urine, were determined in STZ-induced DN mice after the 8th week of STZ administration. The level of inflammatory mediators in the serum and oxidative stress parameters in the tissue homogenate was esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Diosmetin treatment caused a significant decrease in the levels of inflammatory cytokines in the serum of streptozotocin (STZ)‐induced diabetic nephropathy mice. The anti‐inflammatory effect of diosmetin was mediated by the Akt/NF‐κB/iNOS signaling pathway (Jiang, Liu, Zhou, Liu, & Liu, ). Diosmetin suppressed LPS/D‐galactosamine (D‐GalN)‐induced production of inflammatory mediators and cytokines, for example, iNOS, prostaglandin E2, cyclooxygenase‐2, TNF‐α, IL‐1β, and IL‐6, which was regulated by NF‐κB and mitogen‐associated protein kinases (MAPKs) signaling pathways (Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Diosmetin treatment caused a significant decrease in the levels of inflammatory cytokines in the serum of streptozotocin (STZ)‐induced diabetic nephropathy mice. The anti‐inflammatory effect of diosmetin was mediated by the Akt/NF‐κB/iNOS signaling pathway (Jiang, Liu, Zhou, Liu, & Liu, ). Diosmetin suppressed LPS/D‐galactosamine (D‐GalN)‐induced production of inflammatory mediators and cytokines, for example, iNOS, prostaglandin E2, cyclooxygenase‐2, TNF‐α, IL‐1β, and IL‐6, which was regulated by NF‐κB and mitogen‐associated protein kinases (MAPKs) signaling pathways (Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that Akt/NF‐κB signaling pathway is implicated in the pathogenesis of DN and might be a therapeutic target for DN. For instance, diosmetin protects against renal injury in STZ‐induced DN by modulating the Akt/NF‐κB/iNOS signaling pathway in mice (Jiang, Liu, Zhou, Liu, & Liu, ). Andrographolide ameliorates DN by attenuating hyperglycemia‐mediated renal oxidative stress and inflammation via inhibiting the Akt/NF‐κB pathway in mice (Ji et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…At the end of animal experiments, the serum samples were collected and the serum BUN and creatinine levels were measured to evaluate kidney function by using commercially available kits (Nanjing Jiancheng Bioengineering Institute, Nanjing, China) in accordance with the manufacturer’s protocols [ 29 , 75 ]. The absorbance for serum BUN was analyzed at 640 nm by a microplate reader.…”
Section: Methodsmentioning
confidence: 99%